Making Sense out of Nonsense: The Deconstruction of State-Level Sex Offender Residence Restrictions - Meloy, Michelle L. (American journal of criminal justice, 2008)
Releasing a sex offender from prison or placing the offender on community-based sanctions, only to have the offender commit a new sex crime, is a policy-maker’s worst nightmare. Fueled by misperceptions and public fear, sex offender laws have developed piecemeal and without rigorous empirical insight and testing. While policies and practices are well-intended, they are unlikely to resolve the very real social problem of sexual violence and may inadvertently increase victimization. Such is the possibility with residence restrictions. This type of law is among the newest in an ever-growing barrage of legislation designed specifically for sexual criminals yet what little research that exists suggests there is no correlation between residence and sexual recidivism. This article identifies 30 states with state-level residence restrictions and conducts a content analysis of each state’s legislation. Geographical and other assessments are also conducted.